"FORMATION OF THE SPATIAL IMAGINATION OF CADETS IN THE PROCESS OF PASSING THE DISCIPLINE" DRAWING GEOMETRY AND ENGINEERING GRAPHICS - Djumabaev X.Y (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in the formation of spatial representations of Cadets, objects of being and a drawing on a plane, a scheme, a model, a picture, etc.G.by observing and analyzing them, they realize their characteristics and acquire in their minds the initial knowledge about them, perceiving their abstract images. To perceive them, it will be necessary not just to look at the given image, but to be able to read the images, to realize the features of vision by restoring them in space, that is, to analyze visual information. It is important to evaluate the main indicators of the formation of the spatial imagination of cadets. There are such indicators of spatial imagination as stability, width, flexibility, depth, completeness, orientation to the goal, dynamism of the image of a geometric object. The meeting of these clairvoyants expresses the complete and comprehensive formation of the spatial thinking of cadets.